Do whales really increase the oceanic removal of atmospheric carbon? - Meynecke, Jan-Olaf; Samanta, Saumik; de Bie, Jasper; Seyboth, Elisa; Prakash Dey, Subhra; Fearon, Giles; Vichi, Marcello; Findlay, Ken; Roychoudhury, Alakendra; Mackey, Brendan (Frontiers in Marine Science, 2023)
Whales have been titled climate savers in the media with their recovery welcomed as a potential carbon solution. However, only a few studies were performed to date providing data or model outputs to support the hypothesis. Following an outline of the primary mechanisms by which baleen whales remove carbon from the atmosphere for eventual sequestration at regional and global scales, we conclude that the amount of carbon whales are potentially sequestering might be too little to meaningfully alter the course of climate change. This is in contrast to media perpetuating whales as climate engineers. Creating false hope in the ability of charismatic species to be climate engineers may act to further delay the urgent behavioral change needed to avert catastrophic climate change impacts, which can in turn have indirect consequences for the recovery of whale populations. Nevertheless, whales are important components of marine ecosystems, and any further investigation on existing gaps in their ecology will contribute to clarifying their contribution to the ocean carbon cycle, a major driver of the world’s climate. While whales are vital to the healthy functioning of marine ecosystems, overstating their ability to prevent or counterbalance anthropogenically induced changes in global carbon budget may unintentionally redirect attention from known, well-established methods of reducing greenhouse gases. Large scale protection of marine environments including the habitats of whales will build resilience and assist with natural carbon capture.